Digital puppetry of wayang kulit Kelantan: A study of its visual aesthetics / Khor Kheng Kia - Khor, Kheng Kia (2014)
Wayang kulit Kelantan, a form of traditional shadow puppet theatre in Malaysia, is threatened with imminent extinction yet no significant attempts were made to preserve this cultural heritage. It is clear that with the current situation in Malaysia and the level of official support, wayang kulit Kelantan is unlikely to last long. Several researchers have suggested that traditional wayang kulit Kelantan to be digitalised into digital media so that it could be watched on the media screen in order to provide greater accessibility and flexibility. The digital puppetry of traditional wayang kulit Kelantan is very helpful in promoting this art form and also indirectly by preserving it via alternative media. This study aims to examine the possibilities and probe potentials of using Computer Graphics (CG) and modern technology to preserve the visual aesthetics of traditional wayang kulit Kelantan. The coverage of the study consists of three major aspects, namely: (i) the visual aesthetics of traditional wayang kulit Kelantan, (ii) Computer Graphics (CG)/ motion capture and (iii) digital puppetry. This study provides in-depth information and explanations on two major aspects. The first aspect is the identification and description of the facets of the visual aesthetics of traditional wayang kulit Kelantan; emphasizing its principal puppet designs and shadow images. The second aspect is the use of modern technology and CG to capture these facets into digital media. Three computer experiments have been carried out in this study. Both key-frame animation techniques and motion capture facilities have been employed in these experiments. This study serves as a contribution to preserve and revitalize traditional wayang kulit Kelantan through the use of digital technology and modern media. It presents and ii provides solutions on issues that have to be addressed in the production of digital puppetry of traditional wayang kulit Kelantan.